Late onset endophthalmitis associated with intraocular lens: a case of molecularly proved S. epidermidis aetiology. Issue 7 (July 1991) - Jansen, B.; Hartmann, C.; Schumacher-Perdreau, F.; Peters, G.
Abstract : A case of severe endophthalmitis after cataract extraction followed by posterior chamber lens implantation is reported. Microbiological cultures from a tap of the patient's aqueous humour prior to lens explantation as well as from the explanted lens and aqueous and vitreous humour during operation yielded Staphylococcus epidermidis sensu stricto. Scanning electron microscopy showed massive colonisation of the lens loop by staphylococci. Clonal identity of all isolates was demonstrated by plasmid DNA analysis and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) of extra-cellular products. This is strongly suggestive of the aetiological role of S. epidermidis in this case of late onset endophthalmitis.